PowerPoint Slide–Based Instruction for Shorof: Development and Classroom Trial in Islamic Junior High School - Mansya'ul Fitriyah; Subhan Subhan; Nurhamim Nurhamim (Lingu, 2025)
Purpose – This study aims to design and validate PowerPoint slide-based learning media for the subject of Shorof (Arabic morphology) and to determine its suitability and effectiveness for class VIII students at Darul Hikmah Islamic Junior High School Syekh Ciliwulung Serang, Banten. Design/methods/approach – A research and development approach organized by the ADDIE cycle guided iterative specification, expert validation, revision, and classroom trial. The population comprised 99 Grade VIII students; a purposive sample of 33 students (IPS-1) participated in a limited trial. Instruments included expert review rubrics, pre/post assessments aligned to derivational patterns, affixation, and morphophonemic adjustment, and structured observation/interview protocols. Descriptive statistics, normalized gain, and paired comparisons were used to analyze learning outcomes and feasibility evidence. Findings – Expert feasibility was very high—94% for content and 98% for media—indicating strong curricular alignment, linguistic clarity, and classroom usability. Mean scores improved from 77.8 (pre-test) to 94.8 (post-test), yielding an absolute gain of +17.0 points, a relative increase of +21.9%, and a normalized gain of g = 0.77 (high). Mastery (≥ 75) rose from 63.6% (21/33) to 100% (33/33). Inferentially, the mean paired difference was +17.12 with t = 11.60, p < 0.001, 95% CI [14.11, 20.13], and a large effect size (d = 2.02). The results suggest that visually coherent, interactive, and procedurally explicit slides clarify tashrīf operations and support universal attainment. Research implications – The validated slide package and accompanying implementation workflow offer a practical pathway for modernizing lower-secondary Shorof instruction through structured multimedia and routine formative checks. For scaled adoption, schools should pair the slides with teacher guidance, fidelity monitoring, and accessibility-oriented refinements. Future research should employ controlled or quasi-experimental, multi-site designs with delayed post-tests for retention/transfer, expanded psychometric reporting, and cost–fidelity analyses, and compare blended, flipped, and AR-augmented variants to optimize impact across contexts.